Analisis Pelayanan Check-In Counter Maskapai Wings Air Kepada Penumpang Di Bandar Udara Muhammad Salahuddin Bima - Ratnah Wati, Siti; Mutiara Hapsari, Cinthia (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2024)
Air transportation is a vital sector for the Indonesian economy, considering the thousands of islands spread from Sabang to Merauke. Sustainable development of air transport by the government, including increasing customer satisfaction, is essential. Sultan Muhammad Salahuddin Bima Airport in NTB only serves domestic flights and is an important hub on Sumbawa Island. Wings Air, operating since 2003, focuses on domestic flights with several international routes. This research evaluates Wings Air's check-in counter service at Sultan Muhammad Salahuddin Bima Airport, with a focus on factors that influence passenger satisfaction. Data was collected through observation, interviews and literature study. It was found that Wings Air's check-in counter service was quite good but still faced several obstacles, such as system delays and lack of officer time discipline. These obstacles result in queues building up and stress for passengers. The research conclusions show the need for improvements in check-in counter services to increase efficiency and passenger satisfaction. Implementation of stricter procedures and further training for check-in officers is recommended so that services can be improved optimally. Keywords: Service, Check In, Satisfaction